2011
DOI: 10.1007/s10549-011-1699-4
|View full text |Cite
|
Sign up to set email alerts
|

The tamoxifen metabolite norendoxifen is a potent and selective inhibitor of aromatase (CYP19) and a potential lead compound for novel therapeutic agents

Abstract: To improve the treatment of breast cancer, there has been a need for alternative aromatase inhibitors (AIs) that bring about adequate aromatase inhibition, while limiting side effects. Since two tamoxifen metabolites have been documented as AIs, we tested a wide range of tamoxifen metabolites on aromatase in order to better understand structural interactions with aromatase and constructed structure-function relationships as a first step toward the development of novel inhibitors. The ability of ten tamoxifen m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
59
1
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 42 publications
3
59
1
2
Order By: Relevance
“…In this first study published, the inhibition of CYP2C19 activity by norendoxifen in human liver microsomes using R-omeprazole as a substrate probe was very weak, with ,25% enzyme activity reduced when the concentration of norendoxifen was 5 mM. No inhibition of CYP2B6 or CYP2D6 by 5 mM norendoxifen was detected (Lu et al, 2012b).…”
Section: Introductionmentioning
confidence: 92%
“…In this first study published, the inhibition of CYP2C19 activity by norendoxifen in human liver microsomes using R-omeprazole as a substrate probe was very weak, with ,25% enzyme activity reduced when the concentration of norendoxifen was 5 mM. No inhibition of CYP2B6 or CYP2D6 by 5 mM norendoxifen was detected (Lu et al, 2012b).…”
Section: Introductionmentioning
confidence: 92%
“…Major side effects associated with tamoxifen use are hot flashes, as well as increased incidence of endometrial cancer and deep venous thrombosis. Besides acting as SERMs, it has been found that some of tamoxifen's metabolites also act as aromatase inhibitors in vitro [2] .…”
Section: Topic Highlightmentioning
confidence: 99%
“…17 Norendoxifen competitively inhibits recombinant human aromatase with an IC 50 of 90 nM. Norendoxifen also shows good selectivity toward aromatase among other CYP450 enzymes, including CYP2B6, 2C9, 2C19, 2D6, and 3A.…”
Section: Introductionmentioning
confidence: 96%